New summation and transformation formulas of the Poisson, Muntz, Mobius and Voronoi type - Semyon Yakubovich (2015)
Starting from the classical summation formulas and basing on properties of the Mellin transform and Ramanujan's identities, which represent a ratio of products of Riemann's zeta functions of different arguments in terms of the Dirichlet series of arithmetic functions, we obtain a number of new summation formulas of the Poisson, Muntz, Mobius and Voronoi type. The corresponding analogues of the Muntz operators are investigated. Interesting and curious particular cases of summation formulas involving arithmetic functions are exhibited. Necessary and sufficient conditions for the validity of the Riemann hypothesis are derived.